Informed Consent on Medical Action in the Beauty Sector Based on Legal Review - Franky Sumarlie (Borong Newinera Publisher, 2020)
The development of medical action not only in clinics, but also in beauty clinics, requires a standard regarding informed consent. This study used 2 problem formulations, namely: 1. The essence of Informed Consent, 2.Informed Consent in Aesthetic Beauty Actions. This study used a Statue Approach, and a Conceptual Approach. The result of this study was that Informed Consent should be a process from the doctor explaining the action until the patient accepts/rejects the action, either in oral or written form. In practice, medical action for beauty at Aesthetic Beauty Clinic was carried out in accordance with professional standard and standard operating procedures. The relationship that arises between the doctor and the patient is called a therapeutic agreement. In this agreement, an approval for a medical action that is given by the patient appears as a form of approval for aesthetic beauty medicine action which is initiated by an offer of the doctor.